Triazenos N-óxidos e seus complexos de Au(I) e Pd(II): uma abordagem no contexto da engenharia de cristais - Moraes, Guilherme Alves de (2018)
This work presents the synthesis of several molecular models, divided into four chapters, and which were strategically synthesized for application in Crystal Engineering. In the first chapter the synthesis of a series of 1-(4-halophenyl)-3-phenyltriazene-N1-oxides (1-4) is shown. This series together with 1-(phenyl)-3-phenyltriazene-N1-oxide (5) had their respective crystallization mechanisms evaluated using the supramolecular cluster as the demarcation of the study. Compounds 1 and 4 show crystallization in two main steps, while compounds 2 and 3 have three main steps. The process of crystallization for 5 occurs in three main stages. Normalized parameters were used to assisted in the interpretation of the crystallization process - NCG% (provides the percentage of topological contribution and energy) and NG/NC (provides the dominant parameter in the step). In addition, the interaction X∙∙∙π was specifically analyzed by geometric criteria and by QTAIM. It was demonstrated the existence of these interactions and observed as a consequence of a topological process and without important contributions to the formation of crystals. In the second chapter a series of unpublished Au(I) complexes (6-9) were synthesized, starting from 1-4. The compounds had their intramolecular interactions of type C-H···Au and Au···O evaluated by geometric criteria and by QTAIM. It was possible to confirm the interaction C-H···Au in the compounds and classifies them as anagostics. The Au···O interaction was distinct, presenting the lowest distance values reported in the literature. This interaction facilitated the occurrence of the CH ···Au interaction. In the third chapter a series of unpublished complexes {bis-[1-(4- halophenyl)-3-phenyltriazenidoyl-N-oxide-k2 N1, O4]palladium(II) (10-13) was synthesized from 1- 4, and had their respective crystallization mechanisms evaluated. All the compounds of the series presented crystallization mechanism in two main stages, involving formation of columns and their approximation. In the last chapter a series of organometallic complexes of Pd(II) (14-17), from 1-4, were synthesized. Their respective crystallization mechanisms were evaluated. Compound 14 exhibit crystallization mechanism occurring in two main steps while the others compounds occur in three steps.